Amos de los mares : los vikings exploran el Atlantico Norte - Lassieur, Allison; Frenz, Ron.; Barnett, Charles, III. (Mankato, MN : Capstone Press, 2007)
The history of how the Vikings discovered North America. In graphic novel format.
Includes bibliographical references (p. 31) and index.
Keywords: Vikings; Vikings -- Comic books, strips, etc; Comic books, strips, etc; Graphic novels; North America -- Discovery and exploration -- Norse; North America -- Discovery and exploration -- Norse -- Comic books, strips, etc